Pag-tanum kag pag-panguma kang sibuyas a preliminary study on onion production in Miagao, Iloilo, Philippines. - Neodama, Alfie Anthony N.
There are twenty-eight (28) onion-producing barangays in Miagao and three (3) namely Bolocaue, Ta-al and Pungtod Monteclaro were selected as specific venues for this study. Only thirteen (13) onion farmers from these barangays were interviewed; four (4) from Bolocaue as well as in Pungtod Monteclaro and five (5) from Taal. One (1) former employee and one (1) employee of the Municipal Agricultural Office (MAO) of Miagao were consulted . The age range of the total fifteen (15) key informants is 32 to 83 years old. The registration and survey of onion farmers in Miagao by the local MAO, interview schedule and key informant interview were used to gather data for the study. The features of simple commodity production were used to analyze and discuss the characteristics and ways by which bulb onions are produced in Miagao and in three selected barangays. The study found out that bulb onion production in Miagao can be characterized as simple commodity production. The production of the crop started in the area in early 1960s through the efforts of the Department of Agriculture. The results of the research paper facilitate understanding the issues, concerns and problems encountered by some local farmers in the production of onion.